JUDICIAL SCRUTINY OF DERIVATIVE MISCONDUCT IN SOUTH AFRICAN EMPLOYMENT LAW: A CAREFUL APPROACH TO THE DUTY TO SPEAK - S’celo Walter Sibiya; Lizelle Ramaccio Calvino; Desan Iyer (Obiter, 2023)
The concept of derivative misconduct has in the past come to the aid of employers in disciplining employees who are reticent about disclosing information that would support the prosecution of an offence. Though dismissal based on derivative misconduct is designed to target the perpetrators of the original misconduct, the justification is wide enough to encompass those innocent of it, but who through their silence make themselves guilty of a derivative violation of trust and confidence. In applying the concept of derivative misconduct, South African labour courts have placed too much emphasis on the unilateral duty of good faith owed by the employee to the employer rather than the reciprocal nature of the duty and the true realities of South African industrial relations. The ground-breaking judgment of the Constitutional Court in National Union of Metalworkers of South Africa (NUMSA) obo Nganezi v Dunlop Mixing and Technical Services (Pty) Limited (2019) 40 ILJ 1957 (CC) crafted significant principles in relation to the application of derivative misconduct within the context of collective bargaining. This article seeks a critical unpacking of the legal quagmire, which has not been fully addressed by the Constitutional Court, and to provide a way forward that may be adopted by employers to promote a spirit of fairness in the employment relationship.